Modification by glucose of the flocculent phenotype of a Kloeckera apiculata wine strain - Sosa, Oscar Antonio (2008)
We have evaluated the induction of the flocculent phenotype of Kloeckera apiculata by glucose mc1 and propose a pathway involved in carbohydrate flocculation induction. Pulses of glucose were given to cells growing in glucose-poor medium (2 g l-1) and the flocculation percentage was measured. To elucidate the mechanism involved in flocculation induction, cycloheximide was injected into the cultures 120 min before the glucose pulse. 2,4-Dinitrophenol or cAMP was added to the media instead, or simultaneously with glucose, while a protein kinase A (PKA) inhibitor was added 30 min before the glucose pulse. With 20 and 50 g l-1 glucose pulse, the yeast flocculation percentage arises to 55 and 65%, respectively. The quantity of proteins and the reflocculating capacity of a lectinic protein extract from the yeast cell wall increase as the concentration of glucose pulse was higher. Cycloheximide prevented the glucose-induced flocculation, while cAMP or 2,4-dinitrophenol increased it 4- and 5-fold, respectively. PKA inhibitor completely prevented the glucose induction flocculation. The flocculent phenotype of K. apiculata mc1 was induced by glucose and the mechanism seems to imply de novo protein (lectin) synthesis via the PKA transduction pathway. This work contributes to the elucidation of the mechanism involved in flocculation induction by glucose of a non-Saccharomyces wine yeast, K. apiculata, which has not been reported. The induction of flocculation by glucose could be a biotechnological tool for the early removal of the indigenous microorganisms from the grape must before the inoculation of a selected starter strain to conduct the alcohol fermentation.